MANAJEMEN LAYANAN KHUSUS KELAS INKLUSI DI SMPS INKLUSI TPA (TEMPAT PEMPROSESAN AKHIR )JEMBER - ayu, Ayu Zaironi Fauziyah; Feni Selfiana; Sintia Ayu Lestari; Hayisul Imam Sukron; Rofiq Hidayat (ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM, 2023)
Management of special services for inclusive classes is a strategy that focuses on managing and implementing a learning environment where students with various special needs receive the same teaching as other general students in one class. This research aims to understand the planning, organizing, implementing and controlling processes in inclusion classes at SMPS TPA Jember. The research method used is descriptive qualitative, with data collection techniques including observation, interviews and document analysis. The research subjects involved school principals, special guidance teachers, and students. The research results concluded that inclusive classroom management special in the planning stage utilizes assessments to identify classroom needs. Organization in inclusive classes aims to ensure an effective structure with clear duties and responsibilities, to provide quality education to all students. In implementing inclusive classes, the existence of Educational Operational Standards (SOP) cannot be separated because these SOPs ensure the smooth learning process in inclusive classes is in accordance with with predetermined educational standards. And control in inclusive classes involves supervision and the role of the school principal, aimed at ensuring effectiveness and efficiency in the learning process.